PEMBEBANAN JAMINAN FIDUSIA DI INDONESIA DALAM PANDANGAN HUKUM PERLINDUNGAN KONSUMEN - Rahmawati Boty (Ensiklopedia Social Review, 2020)
The term Standard Clause itself is not actually contained in the Civil Code or the Fiduciary Guarantee Law, therefore it needs to be linked to the Consumer Protection Law to formulate and regulate the Standard Clause. For this reason, in this study formulated problems regarding how to implement the imposition of fiduciary security and registration. This research approach method is juridical empirical. Based on the results of the research, it can be concluded that the implementation of charging and registration of fiduciary guarantees electronically is basically the same as a manual system, namely preceded by a consumer financing agreement, binding of fiduciary guarantees by notaries followed by registration which can be carried out directly by a Notary with an online system so as to give birth to a Guarantee Certificate. Fiduciary. The connection between the implementation of fiduciary agreements with consumer protection law lies in the use of standard clauses which in fact deviate from the provisions of Article 18 paragraph 1 of the Consumer Protection Law as well as legal protection for consumers and business actors who are biased and tend to pay attention to the interests of consumers only.